A Mixed‐Valence Tri‐Zinc Complex, [LZnZnZnL] (L=Bulky Amide), Bearing a Linear Chain of Two‐Coordinate Zinc Atoms1. Issue 34 (30th June 2015) - Hicks, Jamie; Underhill, Emma J.; Kefalidis, Christos E.; Maron, Laurent; Jones, Cameron
Abstract Reduction of a variety of extremely bulky amido Group 12 metal halide complexes, [LMX(THF)0, 1] (L=amide; M=Zn, Cd, or Hg; X=halide) with a magnesium(I) dimer gave a homologous series of two‐coordinate metal(I) dimers, [L′MML′] (L′=N(Ar†)(SiMe3), Ar†=C6H2C(H)Ph22Pri‐2, 6, 4); and the formally zinc(0) complex, [L*ZnMg(MesNacnac)] (L*=N(Ar*)(SiPri3); Ar*=C6H2C(H)Ph22Me‐2, 6, 4; MesNacnac=[(MesNCMe)2CH]−, Mes=mesityl), which contains the first unsupported ZnMg bond. Two equivalents of [L*ZnMg(MesNacnac)] react with ZnBr2 or ZnBr2(tmeda) to give the mixed valence, two‐coordinate, linear tri‐zinc complex, [L*ZnIZn0ZnIL*], and the first zinc(I) halide complex, [L*ZnZnBr(tmeda)], respectively. The analogues [L*ZnMZnL*] (M=Cd or Hg), were also prepared, the Cd species contains the first ZnCd bond in a molecular compound. Metal–metal bonding was studied by DFT calculations.